2013
DOI: 10.1155/2013/287519
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome of Multiparous Women Aged over 40 Years

Abstract: Objective. The aim of this study was to evaluate the effect of maternal age on prenatal and obstetric outcome in multiparaous women. Materials and Methods. A retrospective case control study was conducted, including women aged 40 years and over (study group, n = 97) who delivered at 20 week's gestation or beyond and women aged 20–29 years (control group, n = 97). Results. The mean age of women in the study group was 41.2 ± 1.7 years versus 25.4 ± 2.3 years in the control group. Advanced maternal age was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…en 30 and 34 (1) . The authors attribute the higher prevalence of chronic hypertension to vascular compromise with age, which can increase the susceptibility of those mothers to pregnancy-specific hypertension even if hypertension is not clinically recognised (1,11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…en 30 and 34 (1) . The authors attribute the higher prevalence of chronic hypertension to vascular compromise with age, which can increase the susceptibility of those mothers to pregnancy-specific hypertension even if hypertension is not clinically recognised (1,11) .…”
Section: Discussionmentioning
confidence: 99%
“…As for parity, there was no significance for complications in pregnancy. According to some studies, however, multiparity is associated with increased maternal and neonatal risk (14) , and nulliparous women over 40 are at greater risk of complications, such as lower birth weight and shorter gestational age than those who have already had children (11) .…”
Section: Discussionmentioning
confidence: 99%
“…T here is an increasing number of women with pregnancy and childbirth in the fourth decade of life for different reasons. [1][2][3] In United States between 2007 and 2011, birth rates have decreased for all women aged <35 years, unchanged for women aged 35e39 years, and increased for women aged 40e44 years. 4 Several studies have found increased rates of stillbirth, perinatal death, preterm birth, low birthweight, and maternal complications such as gestational diabetes mellitus and hypertension, preeclampsia, and need for interventions such as cesarean delivery among women !40 years.…”
mentioning
confidence: 99%
“…P value of APGAR <7 at 5 minutes was 0.032, which was statistically significant. 14 In the present study, 22 (10%) babies were SGA in the case group and only one (0.5%) baby was born SGA in the control group. The p value was <0.0001.…”
Section: Discussionmentioning
confidence: 38%
“…Study done by Seda A and Gonca B in Turkey, also found that NICU admission was more frequent in babies born to older women although the difference was not statistically significant. 14 Among 71 (30%) cases who had NICU admission, 20 (8%) cases had significant events in NICU, which included sepsis, jaundice, RDS, convulsions and death. Out of 39 (17%) controls shifted to NICU, only 6 (3%) had significant events.…”
Section: Discussionmentioning
confidence: 98%